Measurement Models For Market Risk Management in Nigeria - Banjo Adeola Kudirat; Abere Omotayo Johncally (International Journal of Business Economics (IJBE), 2022)
Market risk is connected with the price fluctuations and other market factor movements on four of the most important economic markets: market of debt securities, stock market, currency market and commodity market. A major factor behind the rapid development of risk measurement and management is the high level of instability in the market in which firms operate. A volatile environment exposes firms to greater market risk, and therefore provides an incentive for firms to find new and better ways of modeling the risk. This paper generally analyses the performance of different models which try to solve, estimate, measure and manage various market risks in order to derive parameters which aid good decision making.